2015
DOI: 10.1111/exd.12699
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of human skin mast cells in situ by lysosomotropic agents

Abstract: Mast cells are known to have a detrimental impact on numerous types of inflammatory skin diseases such as contact dermatitis, atopic eczema and cutaneous mastocytosis. Regimens that dampen skin mast cell-mediated activities can thus offer an attractive therapeutic option under such circumstances. As mast cells are known to secrete a large array of potentially pathogenic compounds, both from preformed stores in secretory lysosomes (granules) and after de novo synthesis, mere inhibition of degranulation or inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…So far, the principle of reducing mast‐cell populations by lysosomotropic agents has mainly been adapted to various mast‐cell types in culture and in other preclinical settings . Here, we have extended the concept into a clinically relevant context, and demonstrate that siramesine clearly reduces the number of mast cells in psoriatic skin ex vivo .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…So far, the principle of reducing mast‐cell populations by lysosomotropic agents has mainly been adapted to various mast‐cell types in culture and in other preclinical settings . Here, we have extended the concept into a clinically relevant context, and demonstrate that siramesine clearly reduces the number of mast cells in psoriatic skin ex vivo .…”
Section: Discussionmentioning
confidence: 84%
“…Subsequently it was shown that siramesine, in addition to its σ‐2 agonist properties, also exhibits lysosomotropic activity . In previous studies, we showed that siramesine can cause permeabilization of mast‐cell granule membranes, leading to the initiation of apoptosis . Here, we evaluated the concept of inducing mast‐cell apoptosis in a clinical setting by exploring whether siramesine can reduce mast‐cell numbers in psoriatic lesions.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For immunohistochemistry, staining with was performed using a monoclonal anti-tryptase antibody, as described previously [27]. …”
Section: Methodsmentioning
confidence: 99%